Biological monitoring of workers with past lead exposure. Biochemical findings. - Corsi, G.; Bartolucci, G. B. (Scandinavian Journal of Work, Environment & Health, 1982)
In 56 subjects with lead exposure that had terminated at least 3 a previously and in a reference group of nonexposed subjects, the behavior of several biochemical indicators of dose and effect were studied. The mean values for blood lead (PbB) (1.4 +/- 0.4 mumol/l), chelatable lead (PbUEDTA) (3.4 +/- 1.5 mumol/24 h) and free erythrocyte protoporphyrin (FEP) (62 +/- 25.2 micrograms/100 ml red blood cells) were found to be significantly higher in the subjects with past lead exposure than in the referents. The cut-off levels (mean + 2 SD calculated for the reference group) of PbB, PbUEDTA and FEP were exceeded in 35.7, 67.9, and 28.6% of the exposed subjects, respectively. A normalization of lead doses and indicators of effect was reached only when the exposure had not exceeded 2 a. The time elapsed after termination of exposure did not significantly reduce the PbB level and PbUEDTA excretion, whereas these parameters correlated significantly with the length of exposure. A close correlation was found between the PbB and the PbUEDTA. Due to poor sensitivity at PbUEDTA values of less than 5.3 mumol/24 h (91% of the cases), PbB and FEP were not useful for subjects whose exposure had terminated more than 3 a earlier. In these cases, only PbUEDTA was capable of revealing elevated active lead deposits.